Campylobacter enteritis and bloody stools in the neonate. Issue 5 (May 1985) - Youngs, E R; Roberts, C; Davidson, D C
Abstract : Within 72 hours of birth three babies had loose stools containing fresh blood, mucus, and Campylobacter jejuni/coli. Campylobacter enteritis should be considered in newborn babies passing blood per rectum.